Saiban tot geya - Tasveer abass (Ferozesons; Lahore, 2000)
"Saiban Tot Geya" by Tasveer Abbas explores themes of betrayal, loss, and resilience, as characters grapple with the collapse of their dreams and the harsh realities of life.